Greenland, Denmark and the debate on missile defense: A window of opportunity for increased autonomy - Kristian Søby Kristensen (Danish Institute for International Studies (DIIS), 2004)
This paper investigates the debate leading up to the joint Danish-Greenlandic decision to allow the US to upgrade its radar at Thule Air Base, ensuring its integration in the American missile defense. By analyzing how this debate is structured in the Danish Realm, the paper argues that the contentious history of the Air Base strengthens the moral position of the Greenlanders and provides them with valuable argumentative assets in the debate. This debate, the paper concludes, presents the Greenlanders with a window of opportunity facilitating negotiations with the Danish Government, the effect of which is further Greenlandic independence and increasing Greenlandic influence on security policy. – – Dette working paper undersøger den dansk-grønlandske debat, der ledte op til beslutningen om at tillade USA at opgradere den amerikanske radar på Thule, således at den kan indgå i det amerikanske missilforsvar. Ved at analysere, hvordan debatten i Rigsfællesskabet er struktureret, viser paper'et, hvordan Thule basens historie styrker grønlændernes moralske position, og giver dem værdifulde argumenter i debatten. Paper'et konkluderer, at debatten om missilforsvar har givet grønlænderne en god mulighed for, igennem forhandlinger med den danske regering, at opnå både udvidet indflydelse på sikkerhedspolitikken og således også øget selvstændighed i Rigsfællesskabet.
Keywords: 330